Acidentes de trabalho atendidos em serviço de emergência Occupational injuries treated in an emergency room - Paulo Sérgio de Andrade Conceição; Itatyane Bispo de Oliveira Nascimento; Patrícia Silva Oliveira; Maria Ruth Moreira Cerqueira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2003)
No Brasil, acidentes de trabalho (AT) são notificados apenas para a Previdência Social, restringindo-se, portanto, aos trabalhadores com carteira assinada, que representam, atualmente, menos da metade da força de trabalho ocupada. Neste estudo transversal, pretende-se descrever os acidentes de trabalho e estimar a sua freqüência dentre os casos atendidos num serviço de emergência de Salvador, Bahia, Brasil. Identificou-se 215 pessoas atendidas por causas externas, das quais 68 (31,6%) eram AT. Verificou-se que 36,8% dos acidentados tinham carteira assinada, e dentre esses, apenas 45,5% tiveram notificação para a Previdência, o que indica o alto nível de sub-registro dos AT, mesmo entre os trabalhadores do setor formal. Registros de serviços de emergência podem ser importante fonte de informação dos acidentes de trabalho, e a extensão das ações de vigilância para estes locais poderá ser um passo importante para um melhor conhecimento da magnitude de ocorrência desses eventos na população. In Brazil, work-related injuries are only reported to the National Social Security data system. Therefore, records are limited to formally hired workers, who represent less than half of the active work force. In this cross-sectional study, cases of work-related injuries were identified and interviewed in an emergency room in the city of Salvador, capital of Bahia State, Brazil, to estimate their frequency and characteristics. Work-related injuries accounted for 31.6% of all injuries from external causes (n = 215). Only 36.8% of these patients reported having a formal job contract, and of these, fewer than half (45.5%) had their injuries reported to the Social Security data system, which indicates extensive underreporting of such important work-related health events, even in the formal sector of the economy. Medical records from emergency rooms can be an important source of information on work-related accidents, and health surveillance needs to be enforced in such health care services. This can also be an important step in obtaining a more complete picture of the occurrence of work-related accidents in Brazil.